Serum HER-2 concentration in patients with primary breast cancer. Issue 4 (3rd February 2006) - Kong, S-Y; Kang, J H; Kwon, Y; Kang, H-S; Chung, K-W; Kang, S H; Lee, D H; Ro, J; Lee, E S
Abstract : Objective: To evaluate whether serum HER-2/neu (HER-2) concentration is a valid index of HER-2 status in women with primary breast cancer, and to establish a normal reference range for serum HER-2 concentration in Korean women. Methods: Serum HER-2 concentration was measured and immunohistochemistry (IHC) and fluorescence in situ hybridisation (FISH) carried out on tissue samples from 86 consecutive female patients. The results of the three datasets were compared. The cut off value of HER-2 concentration was determined from the mean +2SD values derived from the serum of 93 healthy volunteers. Results: The IHC and FISH data were significantly correlated (p<0.01), but neither showed significant correlation with the serum HER-2 data. The cut off value of serum HER-2 was 10.2 μg/l, and the serum HER-2 concentration of patients with primary breast cancer ranged from 5.0 to 17.5 μg/l. Only five patients had a serum HER-2 value above the cut off value. Conclusions: Serum HER-2 concentration cannot be substituted for IHC or FISH to evaluate HER-2 status, nor can it be used as a diagnostic tumour marker in primary breast cancer, considering the low prevalence of serum HER-2 elevation.